Edukasi Gizi dalam Pencegahan Anemia dalam Masa Kehamilan Bagi Ibu Hamil di Dusun Kolebarebatu, Kecamatan Rembon, Tana Toraja - Hayuti Windha Pagiu; Suharnita Wijaya; Hermin Neli (Jurnal Kabar Masyarakat, 2026)
The problem of malnutrition in pregnant women is a health issue that risks causing serious complications, both for the mother and the fetus, such as anemia, premature birth, and low birth weight. Anemia in pregnancy has a negative impact on fetal development, including the risk of miscarriage, premature babies, and suboptimal growth. Globally, anemia is considered a major public health problem in more than 80% of countries, with prevalence in pregnancy reaching more than 20%. This service activity aims to increase pregnant women's knowledge about the importance of nutrition in preventing anemia and other complications during pregnancy. The method used is in the form of health education with a promotive-preventive approach, through interactive counseling and group discussions. The material provided includes the nutritional needs of pregnant women, signs and symptoms of anemia, as well as prevention strategies through the consumption of balanced nutritious foods and adherence to iron supplementation. The results of the activity showed an increase in pregnant women's understanding of the risk of anemia and the importance of maintaining nutritional status during pregnancy. Thus, this activity is expected to support the achievement of a healthy pregnancy, reduce the risk of complications, and ensure the welfare of mothers and babies.